OGG1 methylation mediated the effects of cell cycle and oxidative DNA damage related to PAHs exposure in Chinese coke oven workers. (June 2019) - Fu, Ye; Niu, Yingying; Pan, Baolong; Liu, Yanli; Zhang, Bin; Li, Xuejing; Yang, Aimin; Nie, Jisheng; Wang, Ruisheng; Yang, Jin
Abstract: Previous publications have indicated that polycyclic aromatic hydrocarbons (PAHs) exposures are associated with increased DNA damage and abnormal cell cycle arrest; however, the details of mechanisms remain largely unknown. This study aimed to quantify the associations of 8-oxoguanine DNA glycosylase ( OGG1 ) methylation with urinary PAHs metabolites, DNA damage and cell cycle arrest, and further to assess the role of OGG1 methylation in mediating the association of urinary PAHs metabolites with DNA damage and cell cycle arrest. Urinary biomarkers of PAHs exposure and a marker of oxidative DNA damage (8-hydroxy-2′-deoxyguanosin, 8-OHdG) were measured by high performance liquid chromatography. Cell cycle of lymphocyte was analysed with flow cytometry and OGG1 methylation in venous blood was measured by pyrosequencing. After adjusting for covariates, urinary 1-OHP levels were positively associated with lymphocyte S phase arrest and oxidative DNA damage, while were negatively associated with G0/G1 phase arrest. OGG1 methylation was not only positively correlated with urinary 1-OHP in a dose-responsive manner ( P trend = 0.008) but was also associated with G0/G1 phase arrest ( OR : 0.63, 95% CI : 0.41–0.97), S phase arrest ( OR : 1.55, 95% CI : 1.01–2.40) and oxidative DNA damage ( OR : 1.71, 95% CI : 1.02–2.86). Mediation analysis estimated that OGG1 methylation mediated about 20% of associations between urinary 1-OHP levels and cell cycle arrest and oxidative DNA damage, respectively (all P < 0.05). Our findings suggested that urinary 1-OHP concentrations were associated with cell cycle arrest and oxidative DNA damage by a mechanism partly involving OGG1 methylation. Highlights: Urinary 1-OHP was associated with cell cycle and oxidative DNA damage. OGG1 methylation was associated with cell cycle and oxidative DNA damage. OGG1 methylation showed a positive correlation with urinary 1-OHP. OGG1 methylation mediated PAHs-related cell cycle arrest and oxidative DNA damage.